2021
DOI: 10.3390/math9233067
|View full text |Cite
|
Sign up to set email alerts
|

Systematic Review of the Development of Spatial Intelligence through Augmented Reality in STEM Knowledge Areas

Abstract: This study presents a systematic review (SR) of the literature on the use of Augmented Reality (AR) for the development of spatial skills of secondary and higher education students in the teaching of subjects related to the area of Science, Technology, Engineering and Mathematics (STEM). Numerous researchers have confirmed that students tend to have difficulties in acquiring learning content with a high visual load, which is why AR is being used to improve teaching–learning processes. This paper aims to presen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(8 citation statements)
references
References 51 publications
1
7
0
Order By: Relevance
“…AR is a multimedia technology that is suitable for use in geometry learning [20]. Previous research reported that AR-assisted geometry learning can improve spatial abilities and geometry learning outcomes [21][22][23].…”
Section: Introductionmentioning
confidence: 99%
“…AR is a multimedia technology that is suitable for use in geometry learning [20]. Previous research reported that AR-assisted geometry learning can improve spatial abilities and geometry learning outcomes [21][22][23].…”
Section: Introductionmentioning
confidence: 99%
“…AR has been applied across various scientific disciplines to simplify abstract concepts, making them more accessible to students [24]. For instance, it has been employed to enhance spatial skills in STEM education, promoting spatial skill development [28]. The influence of VR and AR on learning outcomes and knowledge retention has been a focal point.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Kaufmann et al (2000) discussed the application of 3D constructs in mathematics and geometry at the high school and university levels. Dinayusadewi and Agustika (2020) applied AR to geometry materials for elementary school students, and Velázquez and Méndez (2021b) discussed the use of AR in algebra.…”
Section: Introductionmentioning
confidence: 99%
“…This comprehensive review examines the usefulness of AR in the field of mathematical pedagogy. Ibáñez and Delgado-Kloos (2018), Ajit et al (2021), and Velázquez and Méndez (2021b) reviewed AR for STEM (science, technology, engineering, and mathematics), while Ahmad and Junaini (2020) and Jabar et al (2022) studied AR in mathematics learning SLR with basic questions.…”
Section: Introductionmentioning
confidence: 99%